[Cat's Claw (Uncaria tomentosa)] - Jolly, M. (M. Jolly, Trinidad, 2009)
A description on the back of the postcard reads "The "Cat's Claw" enveloping the limbs of gigantic trees forms a scintillating, lacy pattern against the blue sky." Affixed to the back of the postcard is a USA 19 cents stamp. Postcard numbered C5349.
Colour: Coloured; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Uncaria tomentosa--Trinidad and Tobago; Plants--Trinidad and Tobago; 1992